What lessons does the pandemic of COVID-19 teach us about banking liquidity and information share in the CEMAC zone? - Djekonbe, Djimoudjiel; Rostand, Dany Dombou T. (BOHR International Journal of Finance and Market Research, 2024)
This paper examines how the COVID-19 pandemic has influenced both the prevalence of excess liquidity and the degree of information sharing within the CEMAC region’s financial sector. Using monthly data from 2000 to 2023 and applying a Bayesian Vector Autoregression (BVAR) approach. Pandemic-related shocks reduced excessive liquidity by approximately 12% and deposit levels by 8% over a 6-month horizon. These liquidity disturbances were observed to persist over both short- and long-term periods, indicating systemic challenges linked to information asymmetry. Following the onset of COVID-19, there was an uptick in credit provision, coupled with a downturn in equity investment observed after the initial 6-month period of the outbreak. Likewise, in parallel with the decline in equity, the flow of banking information diminished during the pandemic, indirectly supporting an increase in indebtedness. To mitigate these effects, the study recommends addressing information asymmetry by introducing comprehensive credit registries and implementing borrower assistance measures.